ROLE OF COLCHICIN AND MANNITOL IN INDUCING GENETIC VARIATIONS AND DROUGHT TOLERANCE OF BARLEY VARIETIES IN VITRO - Baday , Saja; Hamza, Ibrahim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimed to inducing genetic variations for drought tolerance in vitro for callus three varieties Ebaa265, Ebaa99 and Bouhoth244 of barley (Hordeum vulgare L.) using plant tissue culture technique. An experiment was conducted  in plant tissue culture laboratory at the College of Agricultural Engineering Sciences, University of Baghdad during the years 2022-2023 .The experiment included the use of colchicin at concentrations of (0,2.5,5 and 7.5) mg.L-1 and for a soaking periods of (0,4,8 and 12) hours, and mannitol at concentrations of (0,2,4 and 6) g.L-1 using MS media. The results showed that there were significant differences in the average dry weight of callus before and after colchicin treatment at a concentration of 7.5 mg.L-1 for a soaking period of 12 hours and with mannitol 6 g.L-1 and the comparison treatment. The dry weight of callus before colchicin treatment reached 40.30 mg in the variety Ebaa265, was significant different of the average dry weight of callus after colchicin treatment reached 92.65 mg within the variety Bouhoth244.The PCR-RAPD with five primers (OP-A06,OP-A07,OP-A08,OP-B01 and OP-B02) examination revealed differences in the number of resulting bands and their molecular weights in colchicin treatments and the comparison treatment, in light of the results. It could be concluded that colchicin has the ability to cause genetic variations and increase the tolerance of vegetative growth to drought stress resulting from treatment with the compound mannitol in Barley.